THE POETRY'S POTENCIES AS EMOTION THERAPY MEDIA IN SOCIETY 5.0 - Fatimah, Siti; Ngatmini, Ngatmini; Kurniawan, Latif Anshori (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2021)
(Title: The Poetry's Potencies As Emotion Therapy Media in Society 5.0). This study aims to describe the function of poetry as a medium for emotional therapy in society 5.0. The data from this study are poetry texts written by students. Data were collected through test techniques (poetry writing) and non-tests (interviews, observations, and documentation). Based on the results of the study, it is said that aside from being a medium for brainstorming one's thoughts, feelings and experiences, poetry has the potential to become a medium for emotional therapy. Dictionaries, Enjambments, typography, and arrangement of lines can be said to represent the soul of the poet when angry, happy, in love, traumatized, experiencing sadness, and other emotions. The entire contents of the poem is a reflection of the emotions that the poet naturally experienced, saw, and felt in the packaging of words that were solid and full of meaning.Keywords: poetry, emotion therapy, therapy media, society 5.0